Lived experiences of adolescents living with human immuno- deficiency virus in Namibia - Shelley Schomollgruber; Ndinohokwe Mukerenge (Intelektual Pustaka Media Utama, 2023)
Adolescents living with human immunodeficiency virus (HIV) experience stigma, ill-treatment, and many other challenges due to their health condition. Their experience with HIV is highly overlooked, yet, it shapes their decisions and influences their health outcomes. The objective of this study was to explore and describe the lived experiences of adolescents living with HIV in the Namibian context. We conducted a qualitative study of adolescents (aged 10-19 years) at five different anti-retroviral treatment (ART) clinics in Rundu district, Kavango region Namibia. We used purposive sampling and collected data through in-depth interviews with 21 adolescents from October 2020 to December 2020. We analyzed the data with content analysis. The mean age of participants was 16 years, and the age ranged between 12-19 years. Most participants (62%) have never been in a relationship or engaged in sexual activities. All the participants were in school at the time of the study. The content analysis yielded five broad categories: i) experience with HIV care and treatment, ii) finding out about HIV Status, iii) the interplay between HIV and social relationships, iv) the need for information on HIV and the treatment, v) multiple fears, worries, and means to cope. Adolescents living with HIV (ALWH) experience many challenges due to their health condition. Learning about their HIV status is one of the most challenging experiences. There is a need for continued HIV care and support for adolescents living with HIV, which is adolescent- friendly and focused.